Flaxseed intervention and reproductive endocrine profiles in patients with polycystic ovary syndrome: an open-labeled randomized controlled clinical trial - Najdgholami, Zahra; Sedgi, Fatemeh Maleki; Ghalishourani, Samira Sadat; Feyzpour, Marzieh; Rahimlou, Mehran (Frontiers in Endocrinology, 2025)
IntroductionPolycystic Ovary Syndrome (PCOS), affecting 6–15% of women of reproductive age, is characterized by hormonal imbalances and metabolic disturbances. Flaxseed, rich in omega-3 fatty acids and phytoestrogens, may offer a natural approach to improve reproductive hormone profiles in PCOS patients. This study is aimed at evaluating the effects of flaxseed supplementation on reproductive endocrine profiles in women with PCOS.MethodsIn this open-labeled, randomized controlled trial, 70 women with PCOS were randomly assigned to either the intervention group (n=35), receiving 30 grams of milled flaxseed daily along with lifestyle modifications, or the control group (n=35), receiving only lifestyle modifications, for 12 weeks. The primary outcome was the change in follicle-stimulating hormone (FSH) levels. Secondary outcomes included changes in serum concentrations of luteinizing hormone (LH), the LH/FSH ratio, anti-Müllerian hormone (AMH), estradiol, dehydroepiandrosterone sulfate (DHEAS), and androstenedione.ResultsAfter 12 weeks, the flaxseed group showed a significant increase in FSH levels compared to the control group. FSH levels increased from 9.72 ± 11.95 µU/mL at baseline to 10.59 ± 12.14 µU/mL after the intervention (p = 0.027). The mean treatment effect was 0.87 (95% CI: 0.086 to 1.75). The LH/FSH ratio also significantly decreased in the flaxseed group (mean treatment effect: -0.341, 95% CI: -0.63 to -0.08, p = 0.031). No significant changes were observed in AMH, LH, estradiol, DHEAS, or androstenedione levels.ConclusionFlaxseed supplementation may benefit women with PCOS by increasing FSH levels and decreasing the LH/FSH ratio, suggesting its potential as a complementary intervention for managing hormonal disturbances in PCOS. Further studies are needed to confirm these findings and elucidate the underlying mechanisms.